Family Support With Self-Care Ability In Mental Retardation Children In SLB State 1 Bulukumba - Tenriwati; Haerani; Rahmi Islamiah (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2018)
Mental retardation is a lack of intelligence. Children with mental retardation in addition to having limited intelligence are also limited in their ability to care for themselves so that they need support from their families. From the results of the study conducted by researchers on June 25, 2018, on 30 respondents, who received support supported by the family of 21 respondents and who received less support as many as 9 respondents. while self-care ability, which is capable of 20 respondents who can self-care and 10 poor respondents in self-care. This study aims to determine the relationship of family support with the ability of self-care in children's Mental Retardation in Bulukumba 1 Public Middle School in 2018. The research method uses an analytical design with a